Challenges of Preadolescence in the School Context: A Systematic Review of Protective/Risk Factors and Intervention Programmes - Maria Lidia Mascia; Giulia Langiu; Natale Salvatore Bonfiglio; Maria Pietronilla Penna; Stefania Cataudella (MDPI AG, 2023)
Preadolescence is a critical period, characterised by changes in physical, hormonal, cognitive, behavioural, and emotional development, as well as by changes in social and school relationships. These changes are accompanied by the transition from elementary school to middle school. The literature shows that this transition is one of the most stressful events for preadolescents, which can have a negative impact on their well-being. The main objectives of this review, focused on the school context, were to identify protective and risk factors influencing the well-being of preadolescent students and to describe the interventions implemented. A systematic search of peer-reviewed papers published between 2011 and 2021 was conducted following the PRISMA reporting guidelines. A total of 36 full-text articles met the inclusion criteria. Studies converge in identifying risk factors that may affect student well-being in this age group: individual factors (levels of emotional awareness and self-esteem) and relational factors (friendship, teachers' and parents' supporting actions and roles). Intervention programs are mainly focused on improving emotional and social regulation skills that also influence academic achievement. Our findings have important implications for both research and intervention in school settings.